The Effectiveness of Resource Utilization In Suparvision At Taka Bonerate Natinal Park - Ahmad Difa Awlia Aslim; Muh. Akmal Ibrahim; Muhammad Rusdi (IHSA Institute, 2024)
The utilization of resources in national parks is a subject that is deep and complex, depicting diverse dynamics between environmental protection, economic sustainability, and human recreational needs. As areas considered symbols of natural preservation, national parks often become focal points of debate on how to manage natural resources wisely without sacrificing human needs or damaging fragile ecosystems. From water and energy usage to tourism activities and forest management, national parks provide a unique stage where various interests compete and interact with each other. The data collection methods used are field research in the form of interviews and observations. The types of data obtained are primary and secondary data. The results of this research indicate that resource utilization in supervision at Taka Bonerate National Park is a crucial factor in maintaining environmental sustainability in the region. With the appropriate indicator tools, national park managers can monitor and manage the use of natural resources efficiently and sustainably. Efforts made by the park's superintendent and management team, including increasing the number of field officers, utilizing technology, and collaborating with the local community, contribute positively to enhancing human and material resource utilization in supervision. However, obstacles and challenges such as limited human resources, difficult regional accessibility, and conflicts with the local community remain challenges that need to be overcome. With the right strategies, managers can overcome these obstacles and improve the effectiveness of resource utilization in supervision, thus ensuring the sustainable preservation of the Taka Bonerate National Park environment.